2022
DOI: 10.1167/iovs.63.12.1
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Reticular Pseudodrusen on Choriocapillaris Flow Deficits and Choroidal Structure on Optical Coherence Tomography Angiography

Abstract: Purpose To examine the impact of reticular pseudodrusen (RPD) on choriocapillaris blood flow and choroidal structure in individuals with intermediate age-related macular degeneration (AMD). Methods Individuals with bilateral large drusen underwent optical coherence tomography (OCT), color fundus photography, near-infrared reflectance, and fundus autofluorescence imaging to determine the presence of RPD. These participants also underwent swept-source OCT angiography (SS-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Furthermore, a focal defect in the choriocapillaris overlying pachyvessels was also suggested to be related to pachydrusen [ 32 ]. While previous studies on the relationship between flow deficit in the choriocapillaris/choroid and the phenotype of drusen have been presented [ 14 , 15 ], it is still not clear why soft drusen are uncommon in Asians with darker pigmentation [ 3 ]. The finding of the current study that depigmentation in the inner choroid is more frequent in eyes with soft drusen may provide a new perspective on the role of stroma in the development of AMD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a focal defect in the choriocapillaris overlying pachyvessels was also suggested to be related to pachydrusen [ 32 ]. While previous studies on the relationship between flow deficit in the choriocapillaris/choroid and the phenotype of drusen have been presented [ 14 , 15 ], it is still not clear why soft drusen are uncommon in Asians with darker pigmentation [ 3 ]. The finding of the current study that depigmentation in the inner choroid is more frequent in eyes with soft drusen may provide a new perspective on the role of stroma in the development of AMD.…”
Section: Discussionmentioning
confidence: 99%
“…A linear reduction in choroidal blood flow with aging has been reported in many studies with volunteers [ 6 , 11 ]. While early studies on age-related choroidal changes have focused on the choriocapillaris and choroidal flow [ 12 15 ], in addition to vessels, the choroid is composed of stroma, such as various cells and neurons. Aging changes in choroidal stroma have also been reported in various studies [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, RPD development in AMD could be the result of a choroidal perfusion impairment, as also proved by other similar workgroups [ 45 , 46 ]. On the contrary, Wu et al reported no relevant differences in CC FD and mean choroidal thickness, suggesting that RPD did not alter vascular parameters in intermediate AMD [ 47 ].…”
Section: Octa and Subretinal Deposits In Intermediate Amdmentioning
confidence: 99%
“…However, the period between MNV3 diagnosis and fellow-eye neovascularization was significantly shorter in eyes with RPD than in eyes without [61]. Both RPD and MNV3 patients reportedly share common features such as a high rate of bilaterality, associations with older age and arterial hypertension, a decreased choroidal thickness, and possibly altered CC flow characteristics [62‒67]. In summary, RPD is a striking phenomenon in MNV3 patients, but its cause remains largely unexplained to date.…”
Section: Pathophysiologymentioning
confidence: 99%